11. Berner Kunstausstellung. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1984)
Brunner, Hansjürg ; Daxelhofer, Vinzens ; Holzer, Gerhard ; Koschitz, Norbert ; Salvisberg, Benedikt ; Schnyder, Frédéric ; Tinguely, Jean ; Wiedmer, Paul ; Wilhelm, Anne ; Zahnd, Elisabeth
11. Berner Kunstausstellung, Kunsthalle Bern, 28. Oktober - 25. November 1984
boek